2014
DOI: 10.3233/jad-132633
|View full text |Cite
|
Sign up to set email alerts
|

The Probable Auto-Antigenic Role of Lipids (Anti-Ganglioside Antibodies) in the Pathogenesis of Alzheimer's Disease

Abstract: We examined the sera of 103 demented patients of a mean age of 75 years and 60 age-matched healthy individuals, using ELISA, to investigate the levels of IgM antibodies against GM1, GD1b, and GQ1b gangliosides and their possible correlation with clinical parameters (age, severity, and type of dementia). All the individuals that demonstrated positive titers of anti-ganglioside antibodies were demented patients whereas normal controls showed borderline or negative values. Significant correlation was revealed bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Anti-GM1 AGAs have been found in Alzheimer's disease (AD) patients. 50 AD has been also related to IgM anti-GD1b 51,52 and anti-GQ1bα antibodies, although the latter association has received discordant views in the literature. 53,54 It appears that GM1-amyloid-beta protein complexes have the capacity to increase Aβ assembly.…”
Section: Pathologies Involving Antiganglioside Antibodies (Agas) Neurmentioning
confidence: 99%
“…Anti-GM1 AGAs have been found in Alzheimer's disease (AD) patients. 50 AD has been also related to IgM anti-GD1b 51,52 and anti-GQ1bα antibodies, although the latter association has received discordant views in the literature. 53,54 It appears that GM1-amyloid-beta protein complexes have the capacity to increase Aβ assembly.…”
Section: Pathologies Involving Antiganglioside Antibodies (Agas) Neurmentioning
confidence: 99%
“…In recent years, studies have shown that the homeostasis of lipids in the brain, both cholesterol and sphingolipids (such as gangliosides), are of great importance [ 70 ] with respect to the lipid composition of the cell membrane and the formation of lipid rafts associated with the formation and toxicity of Aβ. These results have renewed the impetus to study the multifaceted role of lipids in amyloidogenesis, neuroinflammation, neuroplasticity, and mitochondrial synaptic function [ 71 , 72 ]. Nevertheless, it remains unanswered whether disturbances of lipid homeostasis observed in AD are the cause or result of the disease [ 70 , 71 , 73 ].…”
Section: Metabolic Disordersmentioning
confidence: 99%
“…It was presented before that antiganglioside reactivity may act as a trigger for neurological damage in patients with systemic autoimmune disorders. A number of diseases associated with AGA have been reported: anti-GM1, anti-GD1b, anti-GQ1b IgM strongly correlated with Alzheimer’s disease, anti-GM3 and anti-GQ1b associated with multiple sclerosis, anti-GM1 with SLE, anti-GM1 or GM1-gliadin complexes with celiac disease, anti-GM2, anti-GD1a, anti GQ1b IgM isotype with HIV infection, anti-GD1b with parvovirus, anti-GM1, anti-GM2, anti-GM3, anti-GD1b, anti -GD1a with type I diabetes, anti -GM1, anti-sulfatide with Sjogren’s syndrome, rheumatoid arthritis, SLE and systemic vasculitis [ 17 , 32 , 34 , 35 , 36 , 37 , 38 , 40 , 41 , 42 , 43 , 44 , 52 , 53 ]. Anti-GM1 and anti-sulfatide antibodies were identified in SLE, idiopathic systemic vasculitis (VAS), Sjogren’s syndrome, and mixed cryoglobulinemia, where they did not correlate with ANA or cryocritus.…”
Section: Discussionmentioning
confidence: 99%
“…Altered expression of sphingolipids is recognized by specific antiganglioside antibodies (AGA). Endogen synthesis of AGA was observed in neoplasia [ 5 , 6 , 29 , 30 , 31 ], viral infections [ 32 , 33 ], in autoimmune diseases like multiple sclerosis, rheumatoid arthritis, Sjogren syndrome, diabetes [ 17 , 34 , 35 , 36 , 37 , 38 ]. AGA were studied in SLE patients, mostly on neuro-psychiatric and peripheric neuropathies, but without concluding results [ 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%